2004
DOI: 10.1017/s0021859605004892
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in insecticide use from adoption of Bt cotton in South Africa: impacts on economic performance and toxic load to the environment

Abstract: The study reported presents the findings relating to commercial growing of genetically-modified Bt cotton in South Africa by a large sample of smallholder farmers over three seasons (1998/99, 1999/2000, 2000/01) following adoption. The analysis presents constructs and compares groupwise differences for key variables in Bt v. non-Bt technology and uses regressions to further analyse the production and profit impacts of Bt adoption. Analysis of the distribution of benefits between farmers due to the technology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 3 publications
0
56
0
Order By: Relevance
“…These studies reported that farmers in Australia, India and China experience reduced health problems as a result of declining pesticide use with Bt cotton and rice [80,[83][84][85]. In contrast, studies by Bennett et al [86] and Debyani and Neeta [87] from South Africa and India reported negative health implications for farmers as a result of adoption of Bt cotton, due to increased toxic exposure and allergic reactions, respectively. Both these studies made the connection between their data and wellbeing, without measuring wellbeing impacts directly.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reported that farmers in Australia, India and China experience reduced health problems as a result of declining pesticide use with Bt cotton and rice [80,[83][84][85]. In contrast, studies by Bennett et al [86] and Debyani and Neeta [87] from South Africa and India reported negative health implications for farmers as a result of adoption of Bt cotton, due to increased toxic exposure and allergic reactions, respectively. Both these studies made the connection between their data and wellbeing, without measuring wellbeing impacts directly.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
“…Both these studies made the connection between their data and wellbeing, without measuring wellbeing impacts directly. Bennett et al [86] connected pesticide exposure to health effects without measuring health effects as such, and Debyani and Neeta [87] reported that farmers have claimed allergic reactions, without independently testing whether such reactions are connected with exposure to Bt cotton. The three remaining bottom-up studies did not connect wellbeing effects with empirical observations at farm or household level.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
See 1 more Smart Citation
“…Famous examples of interventions promoting new technologies and innovations in Africa include the provision of genetically improved crops, such as the new Bt cotton variety (Bennett et al 2004).…”
Section: New Technology and Innovationmentioning
confidence: 99%
“…While advances in biotechnology have continued at a rapid pace, field trials for more than 4000 GM plants have so far resulted in the successful release of only 40 transgenic crops for commercial purposes (Daniell 1999;Brookes and Barfoot 2005). Benefits derived from these GM crops include reduced environment impact due to a decrease in the use of toxic herbicides and insecticides (Bennett et al 2004). Other potential and demonstrated benefits include an increase in productivity, salt/drought tolerance, and disease resistance.…”
Section: Introductionmentioning
confidence: 99%